Menjembatani Visi dan Aksi: Formulasi Strategi dalam Manajemen Pendidikan Islam - Diva Oktavia Mursyidatul Aimmah (Al-Kindi, 2026)
This study aims to examine the strategy formulation process in Islamic education management as a means of connecting the vision and actions of educational institutions. Facing globalization and technological advances, Islamic educational institutions need to develop responsive and relevant strategies without neglecting Islamic principles. This study employed a qualitative approach with library research. Data were obtained from a variety of current literature, including books and scholarly articles, that discuss managerial strategies and values in Islamic education. The analysis shows that strategy formulation plays a central role in guiding institutions to systematically adapt to change. The formulation stages include context analysis, strategy development, implementation, and evaluation. Factors determining the success of a strategy include visionary leadership, participation of all institutional elements, effective communication, an organizational culture based on Islamic values, and adaptability to external environmental dynamics. Through appropriately formulated strategies, Islamic educational institutions can balance managerial efficiency and spiritual orientation, thereby achieving sustainability and benefit in educational management.